Indonesian financial companies' preparedness for the covid-19 pandemic - Tunggal Sari, Cahyani; Suharti, Mamik (Institute of Computer Science (IOCS), 2024)
In order to better understand how debt is used to finance investments and assets in banks and financial institutions' operations prior to, during, and following the Covid-19 pandemic, this research will examine this relationship.All businesses that are registered with the BEI make up the research population. The study's sample consists of 57 financial organizations that are listed on the Indonesia Stock Exchange (IDX) and have complete financial data for the years 2019 through 2021. Purposive sampling was used as the sampling strategy in this study, and the requirements were a financial company's registration on IDX and possession of all 2019–2021 financial data. Using SPSS 26 software, Multiple Linear Regression was used for data analysis. Companies should look into other capital sources, such as utilizing retained earnings, building up depreciation, controlling inventories, controlling cash flow, and other options, in order to boost profitability. Information can be utilized as a decision-making tool for investors. Financial ratio variables and other predictor variables, including management team and majority share ownership, might be added for additional investigation.